Models of Generator Excitation Control Systems in Dynamic Security Analyses of Electric Power Interconnections - Ivanović, Milan V; Popović, Dragan P.; Stojić, Đorđe M.; Veinović, Slavko; Joksimović, Dušan; Minić, Saša (Proceedings, Electrical engineering institute "Nikola Tesla", 2012)
This paper presents models of generator excitation control systems used in dynamic security analyses of electric power interconnections. The general structure and functional block diagram of generator excitation control systems are given, as well as a review of the current state within the electrical power system of Serbia. The model used for analyses of short-term dynamics where transient stability analyses are dominant, has been presented. The model used in the analyses of long-term dynamics, has also been presented. After verification based on experimental measurements, these models have been incorporated into appropriate computer programs for dynamic security analyses of electric power interconnections. These computer programs have been developed at the "Nikola Tesla" Institute and some typical examples of their application have been provided